+0  
 
0
58
1
avatar

Thank you for helping me :)

 May 8, 2021
 #1
avatar+32859 
+1

Vertex 1,-3

 

Parabola vertex form     y = a (x-1)^2 - 3      sub in one of the points (3,2) to calculate 'a'

                                       2 = a (3-1)^2 - 3

                                       2 = 4a - 3

                                         a = 5/4

 

y = 5/4 (x-1)^2 -3     is your parabola    expand it to get the 'quadratic'

f(x) = 5/4 x^2 - 5/2 x + 5/ 4  - 3

      = 5/4 x^2 - 5/2 x - 7/4      

 May 8, 2021

13 Online Users

avatar
avatar
avatar